Transglobal leadership influence on the implementation of sustainable palm oil industry in Indonesia - Ramadhan Subakti; Maria Jacinta Arquisola (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
The company's lack of success in implementation the management of the palm oil industry based on Indonesian sustainable palm oil is thought to be due to a leadership crisis. The purpose of this study is to analyze the intelligence of transglobal leadership on the implementation of sustainable palm oil industry. The research approach used in this study is a quantitative method where data was collected susing a survey to collect primary data and open-ended interview questions to gain further clarity of the problems. Our respondents were 126 employees in the work unit of PTPN VIII who already have ISPO certification. Data analysis used Multiple Linear Regression. Data analysis used Multiple Linear Regression. The results of this study indicate that the intelligence of transglobal leadership has a significant positive effect on the implementation of sustainable palm oil industry. By emphasizing the aspects of business intelligence and global intelligence, it will be a solution in managing the sustainability of the palm oil industry.